TRANSMISSION OF CULTURE AND DEVELOPMENT OF EDUCATIONAL INSTITUTIONS - Sri Hastuti; Firman; Riska Ahmad (Literasi Nusantara, 2021)
This article discusses the cultural transmission and development of educational institutions using references from relevant literature studies. Cultural transmission is the activity of sending or spreading messages from one generation to another about something that has become a habit and is difficult to change. The forms of cultural transmission are acculturation, socialization, and enculturation. Educational institutions exist in the community, living together with community members. Between the community and the school need each other. The community needs students and teenagers in schools, on the other hand, schools need the community to help the learning process at school by providing various kinds of facilities.